2011
DOI: 10.1002/dvdy.22677
|View full text |Cite
|
Sign up to set email alerts
|

Alkali‐like myosin light chain‐1 (myl1) is an early marker for differentiating fast muscle cells in zebrafish

Abstract: During myogenesis, muscle precursors become divided into either fast-or slow-twitch fibres, which in the zebrafish occupy distinct domains in the embryo. Genes encoding sarcomeric proteins specific for fast or slow fibres are frequently used as lineage markers. In an attempt to identify and evaluate early definitive markers for cells in the fast-twitch pathway, we analysed genes encoding proteins contributing to the fast sarcomeric structures. The previously uncharacterized zebrafish alkali-like myosin light c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…This mutation prevents salt bridge formation between residues R281 and D325, thereby destabilizing the myosin head (Budde et al, 2007). Richard et al (2003) reported that changes to the Myh7 genes accounted for 82% of families with identified mutations, emphasizing its relevance for hypertrophic cardiomyopathy The Myl1 gene encodes the fast skeletal alkali myosin light polypeptide 1, and is a specific and early marker for development of fast skeletal muscle (Ling et al, 2010;Burguière et al, 2011). However, several studies also have indicated that Myl1 can be expressed in cardiac muscles including the atria and the left ventricle (Kelly et al, 1995;Franco et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…This mutation prevents salt bridge formation between residues R281 and D325, thereby destabilizing the myosin head (Budde et al, 2007). Richard et al (2003) reported that changes to the Myh7 genes accounted for 82% of families with identified mutations, emphasizing its relevance for hypertrophic cardiomyopathy The Myl1 gene encodes the fast skeletal alkali myosin light polypeptide 1, and is a specific and early marker for development of fast skeletal muscle (Ling et al, 2010;Burguière et al, 2011). However, several studies also have indicated that Myl1 can be expressed in cardiac muscles including the atria and the left ventricle (Kelly et al, 1995;Franco et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal fast specific fibres are formed from the non-adaxial cells in the paraxial mesoderm and genes encoding fast specific components of the sarcomere can be detected in these cells after the 8 somite stage (8 ss) (Burguière et al, 2011). Similarly, expression of six1b can be detected in the same region starting at the 6 ss (Bessarab et al, 2008).…”
Section: Zebrafish Six1 Influences Fast Fibre Formationmentioning
confidence: 99%
“…Kelly and Buckingham [51] have reported that myl-1 expressed in mouse fast-twitch fibres. Burguie`re and his colleagues [28] had reported myl-1 as earliest expressed marker in the fasttwitch precursor cells in the zebrafish embryo, and its knockdown disrupts myogenesis. In P. latipinna, results revealed down regulation of the myl-1 gene at the wound healing and blastema stage while in the differentiation stage it was found to be increased at both transcript as well as protein level suggesting the involvement of myosin light chain 1/3 during muscle contractility for the movement of the fish, P. latipinna.…”
Section: Discussionmentioning
confidence: 99%
“…As the requirement of keratin to get the structural integrity of newly formed epithelium has been reported in many vertebrates during development, adulthood and regeneration [25,26], further analysis of this peptide at transcript level was attempted. For myosin light chain-1, the gene myl-1, encodes two transcript variants expressed in fast skeletal muscle of zebrafish embryo [27] as well as it was reported in the fast twitch fibres and its knockdown has been shown to disrupt myogenesis [28]. Therefore, it was inferred that myosin light chain-1 is important during later stages of regeneration.…”
Section: Introductionmentioning
confidence: 99%